Low-glycemic index cookies supplemented with Cordyceps militaris substrate: Nutritional values, physicochemical properties, antioxidant activity, bioactive constituents, and bioaccessibility - Chanh M. Nguyen; Khoa D. Nguyen; Truc N.T. Tran; Tin H. Trang; N.M.N. Ton; V.V.M. Le; T.T.T. Tran (Food Chemistry: X)
Cordyceps militaris substrate (CMS) is a novel ingredient rich in dietary fibers and bioactive compounds; however, its application in food products remains largely unexplored. This study introduces CMS as a partial wheat flour substitute for developing low-glycemic cookies enriched with dietary fiber and bioactive compounds. Results indicate that CMS supplementation increased fiber and phenolic content by 1.41–2.95 times and 1.30–2.62 times, respectively, compared to unsupplemented cookies. Additionally, carotenoid levels were 15.50–71.34 times higher than those in wheat-based cookies. The simulated digestion system revealed that CMS-supplemented cookies exhibited a low glycemic index (47.9–54.0) while enhancing higher polyphenol and carotenoid release than the controls. Cookies with 15 % CMS supplementation qualified as a “source of fiber”, high-carotenoid, and low-GI food classification while maintaining acceptable sensory attributes. These findings underscore the potential of CMS in food innovation, offering a promising approach to enhancing nutrient intake across populations.